Synthetic Pot: Not Your Grandfather's Marijuana. (March 2017) - Ford, Benjamin M.; Tai, Sherrica; Fantegrossi, William E.; Prather, Paul L.
Abstract : In the early 2000s in Europe and shortly thereafter in the USA, it was reported that 'legal' forms of marijuana were being sold under the name K2 and/or Spice. Active ingredients in K2/Spice products were determined to be synthetic cannabinoids (SCBs), producing psychotropic actions via CB1 cannabinoid receptors, similar to those of Δ 9 -tetrahydrocannabinol (Δ 9 -THC), the primary active constituent in marijuana. Often abused by adolescents and military personnel to elude detection in drug tests due to their lack of structural similarity to Δ 9 -THC, SCBs are falsely marketed as safe marijuana substitutes. Instead, SCBs are a highly structural diverse group of compounds, easily synthesized, which produce very dangerous adverse effects occurring by, as of yet, unknown mechanisms. Therefore, available evidence indicates that K2/Spice products are clearly not safe marijuana alternatives. Trends: SCBs are a large collection of man-made chemicals, reported in the scientific literature over decades of research to have affinity for CB1 and CB2 cannabinoid receptors. Products known as K2 or Spice contain a mixture of SCBs that have been illicitly synthesized and sprayed onto inert plant material, to mimic the appearance and psychotropic effects of Δ 9 -THC in marijuana. K2/Spice products are falsely marketed to adolescent and other vulnerable populations as 'safe' and/or 'legal' alternatives to marijuana, and are widely known to avoid detection in standard drug screens due to their lack of structural similarity to Δ 9 -THC. SCBs present in K2/Spice products produce a variety of dangerous acute and chronic adverse effects, including psychosis, seizures, tolerance, dependence, and death, with a greater severity and frequency than observed following marijuana use. Very little is known about the mechanisms underlying the distinct toxic effects of SCBs compared to Δ 9 -THC, but it is likely that they result from actions at both CB1 and non-CB1 cannabinoid receptor targets.